2013
DOI: 10.1182/blood-2012-12-471904
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin activation synergizes with Pten loss and Myc overexpression in Notch-independent T-ALL

Abstract: Key Points• Wnt activation, Pten loss, andMyc translocation synergize to define a novel subset of murine Notch-independent T-ALL.Wnt signaling is important for T-cell differentiation at the early CD4 2 CD8 2 stage and is subsequently downregulated with maturation. To assess the importance of this downregulation, we generated a mouse line (R26-bcat) in which high levels of active b-catenin are maintained throughout T-cell development. Young R26-bcat mice show a differentiation block at the CD4 1 CD8 1 double-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 56 publications
9
38
2
Order By: Relevance
“…PTEN inactivation in primary samples as well as cell lines reflect results from experimental mouse models, which have shown that c-Myc rearrangements and Pten del exert a synergistic effect in the development of T-ALL, appearing to replace the function of Notch1. 8,16 Interestingly, PTEN del/mut and NOTCH1 mutations were mutually exclusive in our cases, confirming that they arise in different T-ALL subgroups. 17 In a unique TLX1-positive case (no.…”
Section: Genetic Profile Of T-all With Myc Translocationssupporting
confidence: 76%
“…PTEN inactivation in primary samples as well as cell lines reflect results from experimental mouse models, which have shown that c-Myc rearrangements and Pten del exert a synergistic effect in the development of T-ALL, appearing to replace the function of Notch1. 8,16 Interestingly, PTEN del/mut and NOTCH1 mutations were mutually exclusive in our cases, confirming that they arise in different T-ALL subgroups. 17 In a unique TLX1-positive case (no.…”
Section: Genetic Profile Of T-all With Myc Translocationssupporting
confidence: 76%
“…Wnt/β-catenin pathway activation has also been observed in models of MYC-driven liver cancer, suggesting MYC and β-catenin can functionally cooperate during tumorigenesis in diverse tissue contexts (42,43). It has also been reported that lymphomas initiated by activated β-catenin frequently exhibit overexpression of MYC due to genomic amplification or rearrangement and that MYC is required for β-catenin driven lymphomagenesis (44)(45)(46), further supporting a cooperative model for MYC and β-catenin function during tumorigenesis.…”
Section: Discussionmentioning
confidence: 87%
“…However – irrespective of the cue and specific core pathway – cell cycle reentry and progression into the S phase will take place with the consequences unchanged, which can explain why YAP1 and β-catenin are observed in analyses of drug resistance in K-Ras4B cancers [8, 9, 20, 22, 23]. Recent studies of colorectal cancer support the independent and corresponding roles of PI3K and β-catenin in the cell cycle G1 phase.…”
Section: Support For Core Pathways-based Drug Cocktailsmentioning
confidence: 99%